Anisotropic Tomography Beneath Northeast Tibet: Evidence for Regional Crustal Flow - Sun, Anhui; Zhao, Dapeng (Tectonics (Washington, D.C.), 2020)
We present high‐resolution tomographic images of isotropic P wave velocity and azimuthal anisotropy in the crust and uppermost mantle beneath NE Tibet by jointly inverting 62,339 arrival times of the first P and later PmP waves from 6,602 local earthquakes and 9 seismic explosions. Widespread low‐velocity zones in the middle crust contribute most of seismic anisotropy in the crust beneath NE Tibet. The predominant fast‐velocity directions of azimuthal anisotropy are closely correlated with the stress field revealed by GPS observations and focal mechanism solutions in the transition zones among the Alxa block, the Ordos basin, and the Tibetan Plateau. We attribute this feature to regional crustal flow that has intruded northeastward into NE Tibet and possibly affected vertical ground motions, whereas the flow has been resisted by the surrounding rigid blocks and so failed to further extrude eastward between the Ordos basin and the Sichuan basin. The crustal flow is responsible for the intracrust and crust‐mantle decoupling beneath the transition zones of NE Tibet. High‐velocity zones with depth‐consistent anisotropy are found to border the southwestern Ordos basin between 105° and 106°E. The rigid blocks, major active faults (e.g., the Haiyuan, Qinling, and Kunlun faults), and their interactions cause the regional tectonic features and seismic activities. Accommodation of the different deformation patterns and the tectonic interactions may explain the complicated geodynamic evolution of the crust beneath NE Tibet. Plain Language Summary NE Tibet is a hot region for studying far‐field geodynamic evolution of the growing Tibetan Plateau, where deformation patterns remain debated mainly due to the low resolution of seismic results in the crust, especially the middle to lower crust. In order to illuminate the middle to lower crust, we use the Moho reflected PmP wave data of local earthquakes and explosions because the reflected waves have different ray paths from those of the direct P wave data. Seismic anisotropy can provide important information on the nature of deformation associated with tectonic stress. As a result, we determine the first P wave anisotropic tomography of the crust and uppermost mantle under NE Tibet. We find that widespread low‐velocity zones in the middle to lower crust may reflect regional crustal flow beneath NE Tibet. The crustal flow leads to the intracrust and crust‐mantle decoupling and vertical motion in the transition zone, whereas coherent crust‐mantle deformation more likely occurs in the surrounding rigid blocks. Our results shed new light on the complicated tectonics of NE Tibet with accommodation of the different deformation patterns and interactions of tectonic blocks and active faults. Key Points The first 3‐D P wave anisotropic tomography beneath NE Tibet is determined The use of PmP reflected waves greatly improves the resolution of the middle to lower crust Widespread low‐velocity zones in the middle to lower crust may reflect regional crustal flow